From one forger to another, from tall travel tales to a credible legacy (15th century) - França, Susani Silveira Lemos [UNESP] (My University, 2015)
In the 15th and early 16th centuries, when traveling eastward and westward no longer proved extraordinary, travel writings, such as those of Marco Polo or Jean de Mandeville, were printed and reprinted and have been in the world of exchanges and acquisitions both in Portugal and in other parts of Europe. However, although they have played a key role in defining foreign worlds for Europe, reflecting the aspirations of their time and providing news about the universe to be discovered, these reports do not always necessarily tell of trips that were actually taken. Several of them, on the contrary, do no more than draw together, for contemporary readers, passages of interest taken from other writings; passages which, based on their regularity and frequency, would allow for a narrative staged as travel to be taken as truth for contemporaries and immediate successors. In the Iberian Peninsula of the late 15th century, an account written by an author about whom nothing is known, Gomez de Santisteban, who defines himself as a companion of Prince Pedro on a supposed trip to the Holy Land, was among those reports integrated into the description and the perception of the land being discovered. The driving question of this paper is, therefore, how Santisteban, though he wrote memories of trips that he did not take, achieved credibility like those travelers whose trips have been recognized as authentic.
Keywords: 15th century; Imaginary travels; Memor; Portugal; Royal travels